Similarity solutions for laminar convection boundary layer flows from a cone in a porous medium filled with a nanofluid. - Ahmad, Syakila (Universiti Sains Malaysia, 2014)
The steady free and convection boundary layer flows from a vertical cone in a porous medium filled with water based nanofluids are numerically investigated using three different types of nanoparticles which are copper,alumina and titania.